Strategi Pengembangan Danau Tanah Mas Berbasis Analisis SWOT - Rabi'ah Oktaviany; A. Jalaludin Sayuti; Heri Setiawan (Politeknik Negeri Sriwijaya, 2020)
This research is designed to identify the conditions of the internal environment and external environment, as well as the development strategy of Tanah Mas lake. This research uses qualitative descriptive research methods.Â The data sources in this study are primary and secondary data sources, this study uses data collection techniques in the form of interview observations and questionnaires. The study used purposive sampling with 30 respondents. Research data analysis techniques using SWOT analysis. Â SWOT analysis results, is obtained from 16 alternative strategies for developing Tanah Mas Lake, namely S-O strategy: making special packages for events, making special packages for schools, adding officers to make calls for cleanliness, making places to eat in the middle of the lake. W-O Strataegi: Improving facilities and vehicles, making fishing competition activities at least once a month, making souvenir / souvenir facilities, providing secure parking facilities. S-T Strategy: Lake Tanah Mas implements new normal hygiene, health and safety protocols, makes family vacation packages at economical prices, establishes cooperation with travel agents, promotions. W-T Strategy: Lake Tanah Mas makes activities / events once a month, investors, create new vehicles and provide computer facilities for Lake Tanah Mas employees.